2021
DOI: 10.3390/s21030703
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Communication in Biomedical Applications

Abstract: Near-field communication (NFC) is a low-power wireless communication technology used in contemporary daily life. This technology contributes not only to user identification and payment methods, but also to various biomedical fields such as healthcare and disease monitoring. This paper focuses on biomedical applications among the diverse applications of NFC. It addresses the benefits of combining traditional and new sensors (temperature, pressure, electrophysiology, blood flow, sweat, etc.) with NFC technology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Transportation, electrification, medical applications, micromachines, wireless communication and wireless charging are some areas demanding new technology to develop compact and high performance applications; and the manufacturing of low losses magnetic components is key [ 154 ].…”
Section: Magnetic Devices and Miniaturizationmentioning
confidence: 99%
“…Transportation, electrification, medical applications, micromachines, wireless communication and wireless charging are some areas demanding new technology to develop compact and high performance applications; and the manufacturing of low losses magnetic components is key [ 154 ].…”
Section: Magnetic Devices and Miniaturizationmentioning
confidence: 99%
“…Several battery-free, wireless OE devices are demonstrated that utilize near-field communication (NFC) automation [ 152 ] for multicolor light emission and recognition in a way that permits specific evaluation of the optical attributes of the skin—to detect PVD and estimate coloration—and/or of color-responsive materials for environmental recognition [ 153 ]. Explicit cases comprise devices that can monitor pulse, tissue oxygenation, pressure pulse dynamics, UV exposure, and skin color through an integrated collection of time-multiplexed miniaturized LEDs and photodetectors whose signals are amplified and digitized before wireless broadcast [ 154 , 155 ].…”
Section: Skin-like Wearable Sensing Devicesmentioning
confidence: 99%
“…Advanced ion sensors can be integrated with IoT devices for developing portable and wearable sensing platforms [97]. Particularly, wearable sensing platforms have been developed for the analysis of biofluids, including sweat, considering their major advantages such as high efficiency for non-invasive healthcare monitoring and POCT [98,99].…”
Section: Ion Sensorsmentioning
confidence: 99%